Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

1 Comment Already

mygif
Roger the Mole Said,
February 5th, 2011 @4:05 pm  

Rearrange into standard form:
3m^2 + 6m – 3 = 0
a = 3, b = 6, c = -3
m =( -6 ± ? ((6)^2 – (4)(3)(-3))) / 2(3)
m =( -6 ± ? (36 + 36) / 6
m = ( -6 ± 6 ?2) / 6
m = -1 ± ?2

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved